COMPARATIVE STUDY ON MYTH BETWEEN CHINESE AND ARABIC: PHOENIX AS AN EXAMPLE - Ye Xinyu; Associate Prof. Muhammad Anas AL-Muhsin, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The myth of a nation reflects the collective memory of the nation and is the source of the philosophy, religion, and literature of the nation. Since the 1930s, mythological research has gradually emerged in China, but there are few comparative studies on Chinese and Arab mythology. Comparative study on myth between Chinese and Arabic: Phoenix as an example in terms of social values and national traits. This article is based on the specific exploration of the mythical image of Phoenix. The records of the Arab world for the phoenix are derived from some ancient Arabic books and this research on Arab mythology starts with basic old books and expands the research materials on Arab mythology. Therefore, providing more research texts for foreign Arab mythological researchers becomes the core task in this article. Under the background of the current research, we seek an updated perspective to focus on the imagery problems in Arab Chinese mythology, especially the image of Phoenix, not only for ancient China and Arab mythology. Research work injects new power, and more importantly, enriches the study of folk literature. This article introduces the meaning of mythology and carries out preliminary preparations such as text analysis, theoretical study, and translation tools, and also discusses the inheritance and development of Chinese Arab folk culture. Folk culture is the foundation of a nation's development. The writing of phoenix in Chinese mythology is an important part of ancient Chinese folk culture. Similarly, it is also important for Arab mythology. In short, the high and profound cultural endogenous and national spiritual connotations of myths better realize the function of cultivating their national spirit.